Plan de marketing estratégico para mejorar las ventas las ventas de la asociación de comerciantes minoristas del mercado “Las Cuadras” ubicado en la parroquia Chillogallo, cantón Quito, provincia de Pichincha - Abarca Guashpa, Daniela Carolina (2015)
This document aims to perform a Strategic Marketing Plan applied to “Las Cuadras” Market as a tool to increase the sales allowing their partners generate higher incomes and improve their life style. The traders of the market association have to know the tools as customer service and the strategic of sales focusing in the presentation and manipulation of products. The theory is based in one of the five marketing management approaches, it refers to the consumer for the determination of conjectural needs and the possible improves that allow the satisfaction of them. The type of investigation applied is descriptive as it allows delineation of mores and customer attitudes, and determining the relation that exist between the different variables existing. The general conclusion is that the external environment of market is favorable for the development of the activities, whereby it is recommended to carry out the implementation of the strategic plan.